Pengaruh Asupan (Natrium, Lemak, Sayur Dan Buah), Dan Tingkat Pengetahuan Terhadap Kejadian Hipertensi Lansia Di Puskesmas Astambul Martapura - Yasir Farhat; Rusmini Yanti (Jurnal Skala Kesehatan, 2021)
Hypertension in the elderly is largely isolated systolic hypertension (HST), increasing systolic pressure causes a greater likelihood of stroke even though the diastolic pressure is within normal limits. Banjar District Health Office recapitulated about elderly that 45 to 59 years old from January to August 2018 in Astambul Public Health Center as many as 1676 people with hypertension incidence as many as 605 people (36.09%). The study purposes was to determine the effect of intake (sodium, fat, vegetables and fruit), the level of knowledge on the incidence of elderly hypertension at Martapura Astambul Public Health Center in 2019. The research type is observational analytic with cross sectional design, the data collected are intake (sodium, fat, vegetables and fruit), level of knowledge, the incidence of hypertension. The population is all elderly with age 45 - 59 years in Martapura Astambul Public Health Centre working are and 98 samples taken by accidental non random sampling, analysis using simple and multiple regression tests. The results showed that most of the elderly both experiencing hypertension and normal, lack of knowledge, no obesity, enough sodium intake, low fat intake, and low vegetable intake and fruit. There is no effect of knowledge level, nutritional status, sodium and fat intake on the incidence of hypertension. There is no effect of vegetable and fruit intake on the incidence of hypertension Keywords: Hypertension, intake (sodium, fat, vegetables and fruit), knowledge, and nutritional status